TRAINING COURSE OF TEACHERS THROUGH THE PROGRAM SEXUAL EDUCATION IN DEBATE IN THE RADIO UDESC FM 100.1 FLORIANÓPOLIS: SOME REFLECTIONS ON THE PERCORRATED WAYS - Marcia de Freitas; Sonia Maria Martins de Melo; Aline Silva Zilli; Andréia Valéria de Souza Miranda (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This article brings up reflections on a collective creative process, which had as a final result the proposal of an extension course project, with the objective of being an alternative mean of awareness and broadening of knowledge and discussions about the subject of emancipatory sexual education. Through radio programs, the course will occupy a space that corresponds to four programs on UDESC Radio FM 100.1, in a weekly schedule that has been taking place for 8 years, called Debating Sex Education. The structure of these programs meets the presuppositions of the Sex Educators Formation Extension Program: interface with technologies - from the EDUSEX group -, which has the aim of providing to the hearers moments of awareness to the possibility of experiences of an emancipatory sex education. The course has the intent of reaching people interested in the subject of  sex education and is committed to discussing the differentiation between sex and sexuality, sex education under an emancipatory perspective, the declaration of sex rights as universal rights and the right to a comprehensive sex education during infancy and adolescence. To instigate and broaden these discussions are paths to be gone through in this project.